1991
DOI: 10.1056/nejm199106133242404
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Precore Region of Hepatitis B Virus DNA in Patients with Fulminant and Severe Hepatitis

Abstract: The presence of a mutant viral strain is associated with and may be involved in the pathogenesis of fulminant hepatitis B and severe exacerbations of chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
293
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(304 citation statements)
references
References 37 publications
6
293
5
Order By: Relevance
“…Although HBeAg positivity in immunocompromised cancer patients appears to be a risk factor for HBV reactivation (Liang et al, 1990;Yeo et al, 2000b), this has not been found to be universally the case (Lok et al, 1991;Nokamura et al, 1996), and an increased risk may be partly attributed to the presence of the precore/core promoter HBV mutant (i.e. HBeAg negative/anti-HBe positive), which had been associated with severe fulminant hepatitis (Omata et al, 1991;Ehata et al, 1993;Liang et al, 1994;Nokamura et al, 1996;Steinberg et al, 2000;Yeo et al, 2000a, b). In addition, consistent with other reports, the baseline (pretreatment) liver function including ALT, total bilirubin and albumin levels did not appear to be associated with the development of HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HBeAg positivity in immunocompromised cancer patients appears to be a risk factor for HBV reactivation (Liang et al, 1990;Yeo et al, 2000b), this has not been found to be universally the case (Lok et al, 1991;Nokamura et al, 1996), and an increased risk may be partly attributed to the presence of the precore/core promoter HBV mutant (i.e. HBeAg negative/anti-HBe positive), which had been associated with severe fulminant hepatitis (Omata et al, 1991;Ehata et al, 1993;Liang et al, 1994;Nokamura et al, 1996;Steinberg et al, 2000;Yeo et al, 2000a, b). In addition, consistent with other reports, the baseline (pretreatment) liver function including ALT, total bilirubin and albumin levels did not appear to be associated with the development of HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it is interesting to find that the use of steroids was an associated risk factor on multivariate analysis. Patients with lymphoma have more frequently been reported to develop HBV reactivation (Lok et al, 1991;Omata et al, 1991;Nokamura et al, 1996;Yeo et al, 2000a), and a recent report on breast cancer patients receiving chemotherapy has shown the viral reactivation rate to be as high as 41% (Yeo et al, 2003). The type of treatment and the type of tumour may be inter-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Because the basal core promoter mutations are generally associated with HBV/C, it could be hypothesized that genotypes B2-B4, containing HBV/C basal core promoter sequence, may lead to increased end-stage liver disease compared to non-recombinant HBV/B. Additionally, the majority of genotype B5 isolates contain the precore G1896A mutation, which is associated with a lowerrisk of HCC compared to wild-type G1896 [76,[80][81]. Understanding these two separate mutation events could explain the lack of HCC and cirrhosis seen in Greenland's, Nunavut's, and Alaska's indigenous populations, where prevalence and genotype distribution for B5 are relatively high.…”
Section: Hbv Epidemiologymentioning
confidence: 99%
“…2,3 The researchers should specify whether the kinetics of HBV DNA and severe hepatitis were associated with precore and/or basal core promoter mutations in the patients with HBV reactivation, because general readers need to be aware of such important viral factors to perform safe monitoring of HBV DNA.…”
Section: Strategy For Preventing Hepatitis B Reactivation In Patientsmentioning
confidence: 99%
“…Huang and his colleagues recently reported on a randomized trial of prophylactic antiviral therapy in lymphoma patients with resolved HBV infection. 2 Although the short-term efficacy in preventing HBV viral reactivation was clearly demonstrated, future studies are warranted to evaluate the optimal duration of antiviral therapy, the high-risk patient population for whom prophylactic antiviral therapy is most indicated, and the effect of prophylactic antiviral therapy on long-term outcome. In the endemic area, the management strategies have to take additional factors, especially cost-effectiveness, into account.…”
Section: Replymentioning
confidence: 99%